(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Among skin malignancies, melanoma leads in terms of mortality. Over the past decades, a steady increase in the incidence of melanoma has been observed compared to other types of malignant neoplasms. If melanoma is diagnosed at an early stage, then relatively high 5-year survival rates can be achieved, which necessitates its timely diagnosis and treatment. Clinical recognition of melanoma, especially in the early stages, can be problematic even for an experienced dermatologist. However, the diagnosis of primary skin tumors is carried out by primary care physicians of various specialties. Melanoma and other malignant skin tumors can be detected during a physical examination when a patient seeks treatment for another condition. When melanoma is suspected, attention is paid to phenotypic risk factors for melanoma development, anamnesis data, and physical examination findings. It is estimated that the sensitivity of clinical diagnosis during a routine examination by an experienced dermatologist is approximately 70 percent. However, the use of diagnostic tools such as dermatoscopes can significantly improve the accuracy of the clinical diagnosis. In recent years, there has been an active search for new, less invasive methods and algorithms for diagnosing skin melanoma. The main goal of non-invasive diagnostics is to determine the need for histological verification of the tumor. The decision to perform histological verification should be based on a combination of clinical and dermatoscopic examination and other information, including growth dynamics, symptoms, and medical history.